Analisis Keputusan Pasien Untuk Dirawat Di Rumah Sakit Umum Daerah Kabupaten Gayo Lues - merna merna (Politeknik Kementerian Kesehatan Banjarmasin, 2019)
Abstract: The quality of hospital services is a form of patient assessment so that it becomes a consideration to decide to be admitted to the hospital. The behavior of patients in making decisions to choose health care facilities in hospitals is influenced by several factors. This study was to analyze patients' decisions to be treated. This type of research is an analytical survey with cross sectional design. The study was conducted at the Gayo Lues Hospital. The population of this study was 4,851 people, the samples were 114 people. Data analysis was univariate, bivariate using chi-square and multivariate using multiple logistic regression at 95% confidence level (a=0.05). The results showed that the factors that influenced the patient's decision to be treated at Gayo Lues Hospital in 2018 were support from community leaders (p=0.018), economic situation (p=0.007), personality (p=0.008), perception (p=0.009), and attitude (p=0.001). While the variables that were not influential were family support (p=0.322), culture (p=0.471), social class (p=0.672), work (p=0.537), motivation (p=0.065). The most dominant factor that influences the attitude of the patient's decision to be treated in Gayo Lues District Hospital is the attitude variable with Exp (B) = 5.982 (95% CI = 2.005-17.847) means that respondents who are positive have the opportunity to decide to be treated at Gayo Lues District Hospital 5.9 times higher than respondents who are negative. The patient's decision to be treated at the Gayo District Hospital is influenced by the support of community leaders, economic situation, personality, perception, and attitude.